Translation Techniques of Humor and Wordplay in the Subtitles of Sergio Pablos' Despicable Me (2010) - Shafa, Nadian; Thohiriyah, Thohiriyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses the translation analysis of exclamatory sentences said by the main character, Belly Conklin, in the novel We'll Always Have Summer by Jenny Han from English to Indonesian. This study aims to analyze and identify the expressions of emotion in exclamatory sentences based on Charles Darwin's theory (1872) of expressions of emotion and to analyze the cultural meaning and pragmatic meaning in the translation of exclamatory sentences based on Yule's theory (1996) of pragmatics. This study uses qualitative methods. The findings show that most of the exclamatory sentences said by the main character express the emotion of joy (54.55%), followed by anger (36.36%) and sadness (9.09%), with no emotion of fear or disgust found. In addition, most of the exclamatory sentences contain both cultural meaning and pragmatic meaning (54.55%), while the rest only contain pragmatic meaning (45.45%), and no sentences containing only cultural meaning were found. The implication of this study emphasizes the importance of understanding the context of the story, culture, and pragmatic aspects in the translation process, especially in literary works. Expressions of emotion can change in intensity in translation, and failure to understand the context can lead to errors in capturing the characters' intentions. Therefore, a thorough understanding of cultural context and pragmatics is necessary to produce accurate and meaningful translation. This study is also relevant in the translation of movie dialogues and other literary texts.